A Retrospective Analysis of Clinical and Epidemiological Aspects of Parvovirus B19 in Brazil: A Hidden and Neglected Virus Among Immunocompetent and Immunocompromised Individuals - Arthur Daniel Rocha Alves; Luciane Almeida Amado (Viruses)
Parvovirus B19 (B19V) infection can affect individuals of all ages, both immunocompetent and immunocompromised. This infection is typically acute and self-limiting, most commonly resulting in rash diseases and acute febrile illness. However, its involvement in atypical manifestations such as chronic kidney disease and acute liver failure have also been reported. Diagnosis of B19V is rarely conducted in these populations, and available studies on its prevalence are limited, outdated, and do not accurately depict the current situation. This study describes and discusses retrospective investigations into the role of B19V in cases of rash diseases, acute febrile illness, anemia, occurring in the context of chronic kidney disease and HIV coinfection, and acute liver failure when no identifiable etiological agent was found, focusing on various populations in Brazil. This overview underscores the importance of recognizing the potential for severe B19V infection in all individuals, regardless of perceived immune status, as well as of considering the possibility of B19V concurrent infection, in both high-risk groups and healthy individuals to reduce the risk of serious complications and improve patient outcomes, by considering the inclusion of B19V in the routine of diagnosis and implementing management strategies. This study was limited by the absence of national surveillance data of B19V in Brazil and by the analyses that occurred retrospectively.